China's provinces and the Belt and Road Initiative - Mierzejewski, Dominik (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book discusses the Belt and Road Initiative at the provincial level in China. It analyses the evolution of the role of local governments in Chinese foreign policy since the opening of China's economy in 1978, showing how the provinces initially competed with each other, and how the central government was forced to react, developing more centralised policies. Unlike other books on the Belt and Road Initiative, which focus on the international aspects of the initiative, this book demonstrates the importance of the Belt and Road in reinforcing China's unitary status and for managing and coordinating development at the local level as well as centre-province relations and province to province relations inside China"--
Understanding the Belt and Road Initiative through central-local perspectives -- The bridgeheads' actions under the BRI : Heilongjiang and Yunnan case studies -- Sichuan and Chongqing : internal integration, Eurasian land bridge and foreign policy -- Guangdong and Hainan : urbanization, maritime economies and strategic encounters under the Maritime Silk Road.
OCLC-licensed vendor bibliographic record.
Keywords: Yi dai yi lu (Initiative : China); Chinese provinces -- Economic conditions; Regional economics -- China; Central-local government relations -- China; State governments and international relations -- China; China -- Economic policy -- 2000-; China -- Foreign economic relations; China -- Politics and government -- 2002-; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research